Antidepressant Effect of Alpha Lipoic Acid in Rats Exposed to Chronic Unpredictable Mild Stress: Putative Role of Neurotransmitters and 5HT3 Receptor - Likhit Akotkar; Urmila Aswar; Rashmi Patil; Dileep Kumar; Manoj Aswar; Jyoti Pandey; Shailendra Gurav (MDPI AG, 2023)
Depression is a neuropsychiatric disorder characterized by altered emotion and cognition. Alpha lipoic acid (ALA) is a potent natural antioxidant and exhibits neuroprotective effects. However, its antidepressant activity and its mechanism of action in rats exposed to chronic unpredictable mild stress (CUMS) need to be evaluated. The rats were divided into six groups. Group, I vehicle control (without stress), II- CUMS, III- fluoxetine (FLX) (50 mg/kg p.o.), IV, V, and VI were treated with ALA (50, 100, 200 mg/kg, p.o.), respectively. All the groups, except I, were subjected to CUMS + treatments from day 1 to day 42. Body weight and behavioral parameters like sucrose preference test (SPT), Morris water maze (MWM), resident intruder test (RIT), and marble-burying test (MBT) were performed on day 0, day 21, and day 42, and forced swim test (FST) on last day 42 and 43 only. The rats were further sacrificed for biochemical and histopathological evaluation. ALA significantly improved behavioral function, increased antioxidant strength, reduced lipid peroxidation, restored monoamines, and protected CA3 neurons. Further, docking studies revealed strong binding of ALA on the 5HT3 receptor. The study demonstrates that ALA might be exhibiting antidepressant effects in part by restoring monoamines and modulating the 5HT3 receptor.